Analysis of Flow and Pressure Pulsation in Draft Tube of Francis Turbine under Different Guide Vane Opening - REN Haibo; YU Bo; WANG Kui; WANG Luobin (Renmin Zhujiang)
In order to explore the influence of the opening of the movable guide vane on the flow and pressure pulsation in the draft tube of the Francis turbine,the steady and unsteady numerical simulations were carried out by establishing a three-dimensional full-flow channel model of a Francis turbine in a power station in southwest China,and the flow characteristics and pressure pulsation of the draft tube of the Francis turbine under different guide vane opening of the rated head were studied.The results show that with the increase in guide vane opening,obvious alternating vortices appear in the straight cone section of the draft tube,which cause low-frequency pressure pulsation in the draft tube.The uniformity of pressure and velocity distribution in the draft tube gradually deteriorates,and the main frequency amplitude of pressure pulsation at the elbow section of the draft tube increases first and then decreases.The vortex zone of the draft tube causes the pressure pulsation of low frequency and high amplitude in the draft tube.